2009
DOI: 10.3233/nre-2009-0509
|View full text |Cite
|
Sign up to set email alerts
|

Motor function and participation among Nigerian stroke survivors: 6-Month follow-up study

Abstract: The pattern of and relationship between motor function and participation among community-dwelling stroke survivors in Ibadan, Nigeria was studied over a 6-month period. Twenty post stroke individuals were recruited out of which 16 (9 males and 7 females) completed the study. Motor function and participation were assessed within 4 weeks after stroke (baseline) and the 2nd, 3rd, 4th and the 5th month at the respective residence of the patients using the Modified Motor Assessment Scale (MMAS) and London Handicap … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 17 publications
1
9
0
Order By: Relevance
“…The finding in this study is similar with the findings of an earlier study where FIM score emerged as an independent predictor of restricted participation (16). Chau et al (17) and Hamzat and Peters (18) also reported an association between functional ability and level of participation. A significant correlation was also found between community reintegration and participation restriction in the participants of this study.…”
Section: Discussionmentioning
confidence: 90%
“…The finding in this study is similar with the findings of an earlier study where FIM score emerged as an independent predictor of restricted participation (16). Chau et al (17) and Hamzat and Peters (18) also reported an association between functional ability and level of participation. A significant correlation was also found between community reintegration and participation restriction in the participants of this study.…”
Section: Discussionmentioning
confidence: 90%
“…Social participation is positively associated with important stroke outcomes such as motor function [16], quality of life [6], and subjective well-being and life satisfaction [5]. Enhancement and optimization of social participation is therefore an essential component of successful stroke care.…”
Section: Discussionmentioning
confidence: 99%
“…Longitudinal studies on after stroke social participation are rare in Nigeria. The only available published data 2 ISRN Stroke emanated from a study conducted across the first 6 months after stroke which reported improvements in social participation over the study period [16]. However, resettling and reintegration of stroke survivors into the community, which is particularly relevant for social participation, often span longer than the first 6 months after stroke.…”
Section: Introductionmentioning
confidence: 99%
“…Various studies (Chau et al, 2009;Raymond at al, 2007;Hamzat and Peters 2009;Mercer et al, 2009) have been carried out on the participation of stroke survivors. Most of the literature on community reintegration after stroke (Pang et al, 2011;Murtezani et al, 2009;Pang and Eng, 2008;Andersson et al, 2008;Beckley, 2006;Hellstrom et al, 2003) appear to focus more on the determinants of community reintegration with little or no emphasis on the influence of gender on community reintegration and stroke-specific characteristics.…”
Section: Introductionmentioning
confidence: 99%